Effect of Zinc Supplementation on Fasting Blood Glucose Control in Burn Injury Patients with Type 2 Diabetes Mellitus: a Case Report - Tedjaatmadja, Chintya; Rasyid, Nurhayati M; Wulandari, Yohannessa; Octovia, Lily Indriani; Sinaga, Wina; Wardhana, Aditya (Writing Center IMERI FMUI, 2023)
Burn injury is the second leading cause of injury in Indonesia. Patients with burn injury may develop zinc deficiency due to loss of exudate and decreased carrier proteins, leading to impaired glucose regulation and inadequate wound healing. Jayawardena et al. showed that zinc supplementation can help regulate blood glucose in patients with diabetes mellitus. This case aims to see the effect of zinc supplementation on fasting blood glucose control in burn injury patients with type 2 diabetes mellitus. A 47-year-old Male with diabetes mellitus and a history of COVID-19 presented with 34% second to third-degree burn injury. The patient was given short-acting insulin 6 IU thrice a day and long-acting insulin 10 IU once a day. Nutrition was increased gradually until it reached 30 kcal/kgBW with protein 1,2 g/kgBW on the 28th day of hospitalization, referring to a diabetes-specific formula, 6x300 kcal. The patient also received zinc sulfate supplementation, 40 mg per day. The patient’s daily zinc intake was 47 mg/dL, and it was analyzed using Nutrisurvey. Fasting blood glucose in the first 28 days was not well-regulated (92-348 mg/dL). After 28 days of zinc supplementation, the patient's fasting blood glucose was stable. (140-180 mg/dL). Uncontrolled blood glucose leads to bacteremia, decreased skin graft takes, and increased mortality. Zinc deficiency can cause greater insulin resistance that can lead to hyperglycemia. Fasting blood glucose was stable after 28 days of zinc supplementation, similar to the previous study. Supplementation can help to regulate fasting blood glucose in burn patients with diabetes mellitus.